Entrepreneurs’ Access to Private Equity in China: The Role of Social Capital - Batjargal, Bat; Liu, Mannie (Manhong) (Organization Science, 2004)
This article examines the effect of entrepreneurs’ social capital on investment decisions of venture capitalists. The empirical data is composed of 158 venture capital decisions in the People’s Republic of China. We found that entrepreneurs’ social capital has significant effects on investment selection decisions of venture capitalists in interaction with growth potential and technology/products of the venture. We also found that strong ties between entrepreneurs and venture capitalists have significant direct effects on investment process decisions such as contractual covenants, investment delivery, and venture valuation.